Implementasi Recursive Failover Pada Mikrotik (Studi Kasus: Lab Komputer Universitas Hindu Indonesia Denpasar) - I Komang Adi Giri Marta; I Kadek Noppi Adi Jaya; Kadek Oky Sanjaya (Program Studi Sistem Informasi, Fakultas Teknologi Informasi dan Sains, Universitas Hindu Indonesia, 2026)
A stable and reliable internet connection is essential for supporting learning activities in computer labs. Disruptions to any single connection can hinder academic activities, making a network redundancy mechanism necessary. This study aims to design and implement a recursive failover method on a Mikrotik router by utilizing two internet connections (dual gateway). The method used is the Network Development Life Cycle (NDLC), which includes analysis, design, simulation, implementation, and monitoring. Testing was conducted using PingPlotter 5 by simulating an outage on one of the ISPs. The results show that the system is capable of automatically switching paths without manual intervention. During a 60-minute observation period, a downtime of 25 seconds and an uptime of 3,575 seconds were recorded, with a network availability rate of 99.30%. This method has proven to enhance network reliability and availability.